Nicholas Cricket - Maxner, Joyce ([s.l.] : Harper Collins, 1989)
Nicholas Cricket and the other members of the Bug-a-Wug Cricket Band lead all the forest creatures in a musical celebration of the night.
Keywords: Crickets -- Fiction; Bands (Music) -- Fiction; Animals -- Fiction; Stories in rhyme